Web Design and Consumer Repurchase Intention: The Roles of E-Satisfaction - Pangestika, Devi Wahyu; Rayhan, Raditya Valeri Aurelia; Mawardi, Wisnu (Scientific Journal of Informatics, 2024)
Objective: Repurchase Intention (RI) becomes one of the frame aspects of customer retention. This study aims to investigate the impact of Web Design (WD) on customers Repurchase Intention (RI) and to evaluate whether E-Satisfaction (ES) serves as a mediator in this relationship. Methods: The research employed a quantitative approach, utilizing purposive sampling to gather data sourced from 124 students from several colleges in Semarang. It conducted a Structural Equation Modeling (SEM) analysis using SmartPLS. Result: The findings of this research show that Web Design (WD) has a significant and positive effect on Repurchase Intention (RI). Additionally, E-Satisfaction (ES) positively influences Repurchase Intention (RI) and serves as a mediator for the beneficial impact of Web Design (WD) on Repurchase Intention (RI). Novelty: The findings of this study provide recommendations for Bukalapak to enhance its Web Design (WD) and ensure high levels of user E-Satisfaction (ES). These strategies can help boost user interest in making repeat purchases on the Bukalapak platform. The novelty in this study lies in the use of diverse range of objects and research methods that are different from previous studies.